2020
DOI: 10.3390/min10121087
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Carbonate Breccia Containing Invisible Gold in Taebaeksan Basin, South Korea

Abstract: The Yemi breccia developed and is distributed within the Paleozoic carbonate rock (Maggol Formation) in the central part of the Taebaeksan Basin, South Korea. Explanation for the genesis of the Yemi breccia has been controversial. We investigated the petrological and mineralogical properties of the breccia and the matrix materials at 60 outcrops. The Yemi breccia is divided into crackle, mosaic, and chaotic breccias based on morphology. In addition, these are divided into blackish, reddish, grayish, and white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The presence of iron, can provide a great diversity of colours to minerals and geomaterials, as known (e.g., [37,38]): goethite, α-FeO(OH), and siderite, FeCO3, form yellow-brown ochre; hematite, α-Fe2O3, depicts a characteristic grey colour when well crystallised and a red tonality in soils (regoliths); vivianite, Fe3(PO4)2•8H2O, displays either a blue or a purple colour [39]; and green tonalities are common for olivine, (Mg,Fe)2SiO4. Moreover, in what concerns sulphides, disseminated pyrite, FeS2, gives a grey colour to a carbonate matrix [40]. The Atlantic Blue ornamental variety, also known as Azul Cadoiço [41], is very similar to Azul Valverde.…”
Section: Geological Setting and Features Of The Bluish-grey Limestonementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of iron, can provide a great diversity of colours to minerals and geomaterials, as known (e.g., [37,38]): goethite, α-FeO(OH), and siderite, FeCO3, form yellow-brown ochre; hematite, α-Fe2O3, depicts a characteristic grey colour when well crystallised and a red tonality in soils (regoliths); vivianite, Fe3(PO4)2•8H2O, displays either a blue or a purple colour [39]; and green tonalities are common for olivine, (Mg,Fe)2SiO4. Moreover, in what concerns sulphides, disseminated pyrite, FeS2, gives a grey colour to a carbonate matrix [40]. The Atlantic Blue ornamental variety, also known as Azul Cadoiço [41], is very similar to Azul Valverde.…”
Section: Geological Setting and Features Of The Bluish-grey Limestonementioning
confidence: 99%
“…The presence of iron in the form of ferric iron, Fe 3+ and ferrous iron, Fe 2+ influences strongly the hue and durability of the stone being limestone's colour related to the FeO/Fe 2 O 3 ratio [57]. Studies regarding the genesis of carbonate breccia in South Korea [40] revealed that the greyish matrix breccia consists mainly of calcite and dolomite, and minor quartz and pyrite and the yellowish part consists of pyrite that was oxidised to goethite or iron oxi-hydroxides.…”
Section: Iron Speciationmentioning
confidence: 99%
“…
The term "breccia" refers to a rock, composed of angular fragments larger than two millimetres, held together by a cement or matrix (Bates and Jackson, 1984). Brecciation results from igneous, sedimentary and tectonic processes or a combination of these (Blount and Moore, 1969;Shukla and Sharma, 2018;No et al, 2020). A breccia often is observed in carbonate rocks and mostly is attributed to dissolution-collapse mechanisms (
…”
mentioning
confidence: 99%